Arthur Miller: A Writer of Tragedy - Smith, Phyllis Shuff (My University, 1967)
The purpose of this study is to prove that Arthur Miller, American playwright, accomplishes his stated aim--the creation of drama similar in purpose and spirit to that of the classical Greeks. This thesis goes a step beyond Miller's statement to maintain that Miller, while achieving his goal, uses the same austere general form that the Greeks employed. Since Miller mentions only one critic of Greek drama by name, H. D. F. Kitto, in his frequent references to the social drama of the Greeks, Professor Kitto's analyses and interpretations of the classical plays are used as the major source for the material on the Greek drama.
Keywords: Miller, Arthur; Tragedy; Literature; Greek Tragedy